ANALISIS TINGKAT KEKRTITISAN LAHAN DI DAERAH TANGKAPAN AIR DI SUB-SUB DAS RIAM KANAN - Nur Anisa Saputri; Eko Rini Indrayatie; Ahmad Jauhari (Universitas Lambung Mangkurat, 2024)
The conversion of agricultural land into built-up land which is unproductive and not in accordance with the capability of the land has the potential to become critical land because it affects the function of the watershed as a regulator of water management and erosion control. This study explains the critical level of land that occurs in the Riam Kanan Watershed (DTA) sub-watershed through a purposive sampling method based on land unit maps that have been overlaid with land cover maps, soil type maps, and slope maps that utilize a Geographic Information System using scoring analysis. The parameters used to analyze the critical level of land in agricultural cultivation areas include productivity parameters, slope parameters, erosion hazard parameters, and management factors. Based on the results of the study, it was found that the criticality level of the land with the category of Critical Potential was 699.43 ha (36.3%) on the land cover of Mixed Dry Land Plantation and mixed gardens, the land with the category of Slightly Critical was 348, 65 ha (18.1%) on rubber plantation land cover and secondary forest, land with Critical category covering 144.47 ha (7.5%) on mixed garden land cover, and land with Very Critical category covering an area of 733.91 ha (38.1%) on scrub and mining land cover.Perubahan lahan pertanian menjadi lahan terbangun dan tidak produktif serta tidak sesuai dengan kemampuan lahan berpotensi menajdi lahan kritis karena mempengaruhi fungsi DAS sebagai pengatur tata air dan pengendali erosi. PeneIitian ini menjelaskan tingkat kekritisan lahan yang terjadi di Daerah Tangkapan Air (DTA) Sub-sub DAS Riam Kanan melalui metode purposive sampling berdasarkan peta satuan lahan yang telah dioverlay dengan peta tutupan lahan, peta jenis tanah, dan peta kelerengan yang memanfaatkan Sistem Informasi Geografi menggunakan analisa skoring. Parameter yang digunakan untuk menganalisis tingkat kekritisan lahan di kawasan budidaya pertanian antara lain parameter produktivitas, parameter kelerengan, parameter tingkat bahaya erosi (TBE), dan manajemen. Berdasarkan hasil penelitian didapatkan tingkat kekritisan lahan dengan kriteria Potensial Kritis (PK) seluas 699,43 ha (36,3%) pada penutup lahan Perkebunan Lahan Kering Campur (PLKC) dan kebun campuran, lahan dengan kategori Agak Kritis (AK) seluas 348,65 ha (18,1%) pada penutup lahan perkebunan karet dan hutan sekunder, lahan dengan kategori Kritis (K) seluas 144,47 ha (7,5%) pada penutup lahan kebun campuran, dan lahan dengan kategori Sangat Kritis (SK)seluas733,91ha (38,1%)pada penutup lahan semak belukar dan pertambangan